Optimizing Sharia Pension Funds: Toward Superior Non-Bank Finance - Zein, Aliman Syahuri; Nasution, Astari Salsabila; Siregar, Aulia Putri; Safitri, Destia Indah; Harahap, Nova Khairani; kholila, Nur; Simbolon, Nurul Faradilla (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Retirement is considered a desire to earn money after working, but the age leading up to retirement is still considered an unproductive time. This research uses literature review to collect, analyze and interpret data from various literature sources. Literature review is an integral part of research. By increasing productivity, raising public awareness, becoming a source of funding for development, and offering more stable investment options, Islamic pension programs can help reduce poverty by improving economic and financial stability in the long run, reducing the burden on the government pension system, and allowing individuals to be more sterile. Non-bank financial institutions use social media to increase public participation in Islamic pension funds by listening, talking, energizing, supporting and embracing. Therefore, social media platforms play an important role in encouraging people to join Islamic pension funds managed by non-bank financial institutions.